2018
DOI: 10.1139/apnm-2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brief intermittent stair climbing on glycemic control in people with type 2 diabetes: a pilot study

Abstract: We examined the effect of brief intermittent stair climbing exercise on glycemic control using continuous glucose monitoring in people with type 2 diabetes (n = 7, 5 men; 2 women; age, 21-70 years). The protocol involved three 60-s bouts of vigorously ascending and slowly descending a flight of stairs. Mean 24-h blood glucose was unchanged after an acute session (p = 0.43) and following 18 sessions over 6 weeks (p = 0.13). The protocol was well tolerated by participants but seemingly insufficient to alter glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…A recent pilot study by Godkin et al . () also reported no impact of an acute bout of brief vigorous stair climbing on subsequent 24 h glucose control, assessed by continuous glucose monitoring (CGM), in participants with T2D. These findings are in contrast to previous interval training studies in which the exercise was of longer duration and higher volume (Gillen et al .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…A recent pilot study by Godkin et al . () also reported no impact of an acute bout of brief vigorous stair climbing on subsequent 24 h glucose control, assessed by continuous glucose monitoring (CGM), in participants with T2D. These findings are in contrast to previous interval training studies in which the exercise was of longer duration and higher volume (Gillen et al .…”
Section: Introductionmentioning
confidence: 83%
“…It is currently unclear whether brief vigorous exercise of different durations and patterns elicits the same response when performed in the postprandial, as opposed to fasted, state but preliminary reports indicate that brief vigorous stair‐climbing exercise performed in the post‐prandial period can acutely lower glucose in participants with T2D (Godkin et al . ). The potential influence of brief vigorous exercise, and possible modifying factors, on acute glucose regulation is depicted in Fig.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of these trials, the one by Bacchi et al (25) had been included in the qualitative synthesis of our 2013 systematic review. We excluded it in the present analysis because the control condition started 24 h after the exercise condition and we could not rule out that the effect of exercise did not persist beyond 24 h. In the study by Godkin et al (30), the effect of a single bout of exercise was compared to control after the first session of exercise and after a session of exercise performed after 6 weeks of exercise training. We only included the effects of the first session of exercise since this was more comparable to the other included studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Although studies have found favorable outcomes in morpho-functional parameters for HIIT training using treadmills and cycle ergometers ~when compared with moderate-intensity exercise [38][39][40][41][42][43] , studies have also shown similarity in aerobic capacity 44,45 , biochemical parameters 46,47 and weight loss 40,48,49 when compared high and moderate-intensity exercises. Hence, the complete details of HIIT training vs. moderate-intensity training remains to be further clarified.…”
Section: Discussionmentioning
confidence: 99%